2017
DOI: 10.21034/iwp.5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wage Inequality and Job Stability

Abstract: How much wage inequality in Brazil is caused by firing costs? To answer this question, I develop and estimate a general equilibrium search and matching model with heterogeneous layoff rates among firms. Using matched employer-employee data from Brazil, I estimate the model, and I find that it replicates the observed residual wage inequality in the data. I simulate a counterfactual removal of existing firing costs, and I find that residual wage inequality drops by 26% as measured by wage variance and by 4.4% as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…One of the most significant challenges faced by low‐wage workers is the risk of job loss. Research has found that low‐wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, ; Lucifora & Salverda, ; Pinheiro & Visschers, ; Stewart, ). Existing evidence also suggests that low‐wage workers have shorter job tenures (Lane, ) and that engagement in low‐wage employment can be a trap for many workers, making the transition from low‐wage work to high‐wage work difficult (Lucifora & Salverda, ; Mason & Salverda, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most significant challenges faced by low‐wage workers is the risk of job loss. Research has found that low‐wage work is associated with higher job insecurity, turnover rates, and unemployment risks (de Araujo, ; Lucifora & Salverda, ; Pinheiro & Visschers, ; Stewart, ). Existing evidence also suggests that low‐wage workers have shorter job tenures (Lane, ) and that engagement in low‐wage employment can be a trap for many workers, making the transition from low‐wage work to high‐wage work difficult (Lucifora & Salverda, ; Mason & Salverda, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, a convergência entre a lei migratória e a lei criminal fundamenta o direito penal do inimigo em razão da coincidência do objetivo de ambas as normas segregarem os indivíduos em categorias de pertencimento e não pertencimento em determinada sociedade que, com frequência, é impactada pela globalização hegemônica e uma política criminal neoliberal (Pessoa;Leal, 2019). Excluise, desta forma, os migrantes alheios e indesejáveis do corpo social com o discurso securitário fronteiriço, crises migratórias, proteção nacional do trabalhador, cultura e economia do país (Jakobs;Cancio Meliá, 2005).…”
Section: A Criminologia Da Mobilidade: Crimigraçãounclassified